Evolving frontier land markets and the opportunity cost of sparing forests in western Amazonia. (15th December 2016) - Holland, Tim G.; Coomes, Oliver T.; Robinson, Brian E.
Highlights: Land markets on forest frontier are highly active even in absence of formal title. Forest cover and year of sale are most important determinants of land price. Over time, properties sold become smaller, less forested, and more expensive. Opportunity cost of forest sparing increases by 9%–27% per year. Abstract: Efforts aimed at sparing forests on tropical forest frontiers through REDD+, PES or conservation initiatives currently rely on a limited understanding of the operation of land markets and their effects on the opportunity cost of forests as frontiers develop. In this paper, we draw on a unique dataset of landholder-reported land transactions that includes post-1991 land sales-in three sub-montane frontier forest areas on the eastern slopes of the Peruvian Andes. We analyze reported land sales that took place between 1979 and 2013 among Amazonian frontier farmers and find highly active land markets in all three areas, often in the absence of formal land tenure. As frontiers developed, parcel size fell, as did the portion of remaining forest cover, and land prices rose, reflecting both forest clearing and general land price inflation as the areas became more populated and developed. Across three study districts in 2013, each additional hectare of forest cleared raised the expected price of a parcel of land by US $1371–$2587. Importantly, we estimate the opportunity cost per hectare of frontier forest rose markedly over time: by $124–$226 per year between 2003 and 2013, a rate of increase over that period of 9–27% per year. Forest conservation programs that rely on estimates of landholders' willingness to accept compensation for sparing forest need to take into account that these values change rapidly as frontiers develop.